It’s A Cow. It’s A Buffalo. No, it’s A Beefalo! Kansas 1886 - Armbrister, Nicole (Kansas State University, The Chapman Center for Rural Studies, 2012)
This paper covers the history of the Beefalo in Kansas, a cross of between the Bison bison and domestic cattle. It explains the reasoning for breeding the two animals to make genetic progress. Extensive scientific and popular literature sources were used.
Nicole Armbrister, “It’s A Cow. It’s A Buffalo. No, it’s A Beefalo! Kansas 1886,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/220.
Keywords: Beefalo; breeding; Central Plains; Charles "Buffalo" Jones; domesticated cattle; Native Americans